Uncovering the Complex Behavior of Hydrogen in Cu2O - WATSON, GRAEME; SCANLON, DAVID (My University, 2011)
The behavior of hydrogen in p-type Cu2O has been reported to be quite unusual. Muon experiments have been unable to ascertain the preferential hydrogen site within the Cu2O lattice, and indicate that hydrogen causes an electrically active level near the middle of the band gap, whose nature, whether accepting or donating, is not known. In this Letter, we use screened hybrid-density-functional theory to study the nature of hydrogen in Cu2O, and identify for the first time the ?quasiatomic? site adopted by hydrogen in Cu2O. We show that hydrogen will always act as a hole killer in p-type Cu2O, and is one likely cause of the low performance of Cu2O solar cell devices.
PUBLISHED
Keywords: Physical chemistry; Cu2O